2019
DOI: 10.1159/000503310
|View full text |Cite
|
Sign up to set email alerts
|

Rapid Estrogen and Progesterone Signaling to Dendritic Spine Formation via Cortactin/Wave1-Arp2/3 Complex

Abstract: Background: Synaptic plasticity is the neuronal capacity to modify the function and structure of dendritic spines (DS) in response to neuromodulators. Sex steroids, particularly 17β-estradiol (E2) and progesterone (P4), are key regulators in the control of DS formation through multiprotein complexes including WAVE1 protein, and are thus fundamental for the development of learning and memory. Objectives: The aim of this work was to evaluate the molecular switch Cdk5 kinase/protein phosphatase 2A (PP2A) in the c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 57 publications
(85 reference statements)
1
1
0
Order By: Relevance
“…Here, we demonstrate that LH disrupts the basal FAK/cortactin/Arp3 subunit interaction and that this effect can be prevented with the specific Src inhibitor (PP2). Similarly, we recently reported that sex steroid treatment diminishes the association between cortactin and the Arp3 subunit in cortical neuron cells (Uzair et al, 2020). We propose that the specific phosphorylation of these proteins affects their interaction as a consequence of physical impediments involving a cycle of binding, phosphorylation, and subsequent dissociation accompanied by FA turnover and cell movement.…”
Section: Discussionsupporting
confidence: 55%
“…Here, we demonstrate that LH disrupts the basal FAK/cortactin/Arp3 subunit interaction and that this effect can be prevented with the specific Src inhibitor (PP2). Similarly, we recently reported that sex steroid treatment diminishes the association between cortactin and the Arp3 subunit in cortical neuron cells (Uzair et al, 2020). We propose that the specific phosphorylation of these proteins affects their interaction as a consequence of physical impediments involving a cycle of binding, phosphorylation, and subsequent dissociation accompanied by FA turnover and cell movement.…”
Section: Discussionsupporting
confidence: 55%
“…Variations in reproductive hormone levels represent an obvious risk factor for postpartum depression (Payne and Maguire 2019 ). Oestrogen and progesterone have been established to influence neuroplasticity in many brain regions, particularly mediating neurogenesis in hippocampal formation (Sheppard et al 2019 ; Uzair et al 2020 ). We confirmed the familiar consequences identified in previous research (Suda et al 2008 ) that animals displayed hopelessness and anhedonia in the escape failure test after inescapable stress and the sucrose preference test after hormone withdrawal (Fig.…”
Section: Discussionmentioning
confidence: 99%